Demo: Towards Flexible and Scalable Indoor Navigation - Shu, Yuanchao; Karlsson, Börje F.; Lin, Yiyong; Moscibroda, Thomas (ACM International Conference on Mobile Computing and Networking (MobiCom), 2017)
Bootstrapping efforts and scalability issues hinder large-scale deployment of indoor navigation systems. We present FOLLOWUS, an easily-deployable (bootstrap-free) and scalable indoor navigation system. In addition to robust navigation through real-time trace-following, FOLLOWUS integrates cloud services to process and combine traces at large scale. It can also leverage optional floor plans to further enhance navigation performance. We designed and implemented FOLLOWUS, including a mobile app and cloud services on Azure, and validate its real-world usability.